2016
DOI: 10.1016/j.pt.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in Helminth Infection: Defenders and Dupes

Abstract: Eosinophilia is a central feature of the host response to helminth infection. Larval stages of parasitic worms are killed in vitro by eosinophils in the presence of specific antibodies or complement. These findings established host defense as the paradigm for eosinophil function. Recently, studies in eosinophil-ablated mouse strains have revealed an expanded repertoire of immunoregulatory functions for this cell. Other reports document crucial roles for eosinophils in tissue homeostasis and metabolism, process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
142
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(150 citation statements)
references
References 86 publications
3
142
1
4
Order By: Relevance
“…Furthermore, expression of MHC-II and co-stimulatory molecules on activated eosinophils following infection with T. muris and Brugia malayi (101, 102) suggests that eosinophils might contribute to establish long-term protection against helminths by promoting adaptive immune responses. However, it has also been shown that host-protective responses remain largely intact in eosinophil-deficient mice following primary infection with S. mansoni, T. muris, S. stercolaris and N. brasiliensis (103). By contrast, mice lacking eosinophils exhibit increased worm burdens after primary infection with H. polygyrus and B. malayi (103), suggesting that the role of eosinophils in promoting immunity may be parasite-specific.…”
Section: Innate Immunitymentioning
confidence: 99%
“…Furthermore, expression of MHC-II and co-stimulatory molecules on activated eosinophils following infection with T. muris and Brugia malayi (101, 102) suggests that eosinophils might contribute to establish long-term protection against helminths by promoting adaptive immune responses. However, it has also been shown that host-protective responses remain largely intact in eosinophil-deficient mice following primary infection with S. mansoni, T. muris, S. stercolaris and N. brasiliensis (103). By contrast, mice lacking eosinophils exhibit increased worm burdens after primary infection with H. polygyrus and B. malayi (103), suggesting that the role of eosinophils in promoting immunity may be parasite-specific.…”
Section: Innate Immunitymentioning
confidence: 99%
“…1,2 The mobilization of mucosal immunity in the context of enteric helminth infection is multi-faceted, complex and intriguing but a comprehensive discussion of such is beyond the scope of this commentary: the reader is referred to excellent recent reviews of this topic. [3][4][5][6][7][8] For the purposes of this review we will use 'epithelial permeability' to denote studies that address the physical properties of the epithelial layer and 'barrier function' is used as a more encompassing term that refers to the many extrinsic (e.g. mucus, IgA, commensal microbiota) components of the intestinal barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on their ability to degranulate and release their cationic granule proteins (which have been shown to kill helminths in vitro ), eosinophils were postulated to have evolved to exert host-protective, helminthotoxic functions. However, multiple studies, including those in eosinophil-deficient or eosinophil-enriched ( Il5 -transgenic) mice, have shown more nuanced roles for eosinophils 5,6 . In many experimental models of helminth infection, eosinophils were not shown to have any protective effects.…”
mentioning
confidence: 99%